The Role of Water Flow and Dispersive Fluxes in the Dissolution of CO2 in Deep Saline Aquifers. Issue 11 (18th November 2020) - Michel‐Meyer, Itamar; Shavit, Uri; Tsinober, Avihai; Rosenzweig, Ravid
Abstract: One of the important mechanisms in CO2 storage is dissolution trapping. The dissolution of CO2 in aquifer brines increases the brine density and leads to hydrodynamic instabilities, formation of CO2 ‐rich fingers, and a desirable acceleration of the CO2 dissolution. In recent decades, there has been an intensive effort to identify suitable deep aquifers for CO2 sequestration. Despite reports that background horizontal flow exists in many of these aquifers, few numerical studies have addressed whether background flow affects the dissolution process. These studies had no available measurements to support their results. Here, we report on laboratory experiments, using a dyed mixture of methanol and ethylene‐glycol (MEG) as a CO2 analog. The effect of an imposed horizontal water flow was investigated by injecting MEG from above into a cell filled with glass beads. An imaging system was used to provide concentration maps, which were analyzed to calculate dissolution rates and to evaluate the characteristics of the convective fingers. The results show that background flow leads to suppression of the fingers' formation, a fivefold decrease of the fingers' wave number, and a twofold decrease in their propagation rate. Therefore, it was expected that the dissolution rate would also be suppressed, consistent with previous numerical results. However, our results show that the dissolution rate was hardly affected by the background flow. We postulate that the horizontal flow results in a trade‐off between the suppression of the convective flux and the enhancement of dispersive fluxes, resulting in negligible net influence on the dissolution rate. Key Points: Although background flow exists in many aquifers that are considered for CO2 storage, its impact on CO2 dissolution was mostly ignored We found experimentally that while background flow reduces the number and propagation speed of the fingers, dissolution rate was unaffected The result is explained by a trade‐off between the suppression of the convective flux and the enhancement of dispersive fluxes